2012
DOI: 10.1002/prep.201100129
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Characteristics of Silicon‐Based Nanoenergetic Formulations with Reduced Electrostatic Discharge Sensitivity

Abstract: This paper details the synthesis and combustion characteristics of silicon-based nanoenergetic formulations. Silicon nanostructured powder (with a wide variety of morphologies such as nanoparticles, nanowires, and nanotubes) were produced by DC plasma arc discharge route. These nanostructures were passivated with oxygen and hydrogen post-synthesis. Their structural, morphological, and vibrational properties were investigated using X-ray diffractometry, transmission electron microscopy (TEM), nitrogen adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 51 publications
2
24
0
Order By: Relevance
“…Several of its material characteristics, including high surface area, energy density, and MEMS compatibility make PS a particularly interesting candidate for the field of energetic materials. Many forms of silicon have been used in energetic applications including silicon particles [8], nanowires and nanotubes [8], and on-chip etched porous silicon [1][2][3][4][9][10][11][12]. The most reactive of these is on-chip PS, which for over twenty years has been known to demonstrate explosive-like reactions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several of its material characteristics, including high surface area, energy density, and MEMS compatibility make PS a particularly interesting candidate for the field of energetic materials. Many forms of silicon have been used in energetic applications including silicon particles [8], nanowires and nanotubes [8], and on-chip etched porous silicon [1][2][3][4][9][10][11][12]. The most reactive of these is on-chip PS, which for over twenty years has been known to demonstrate explosive-like reactions [13].…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Explosive sensitivity is a stochastic variable, which cannot be measured directly because the explosive element is "one shot" element that cannot be tested completely before use. Several special statistical approaches for sensitivity measurements were developed, such as Langlies's method, the Bruceton up-down method, and Neyer's D-optimize based method.…”
Section: Resultsmentioning
confidence: 99%
“…The nanoenergetic composites were prepared by mixing NaClO 4 nanoparticles and the prepared Si powders and then the performance of their combustion was investigated. It was found that the nanoenergetic composite of NaClO 4 nanoparticles and SiNMs at the equivalence ratio of 0.9, in which the surfaces of the SiNMs were passivated with hydrogen, exhibited the highest speed of combustion wave [65]. This indicates that the passivation of the SiNMs with hydrogen is necessary to improve the performance of combustion of the Si-based nanoenergetic composites.…”
Section: Si Nanowiresmentioning
confidence: 95%
“…When the mixture of Si and Fe (catalyst) powders was used in the experiment, the product also contained a little amount of SiNTs [65]. The average diameter and length of the SiNTs are similar to those of the nanowires, but the average thickness (approximately 2 nm) of their SiO shells is thinner than that of the nanowires.…”
Section: Si Nanotubesmentioning
confidence: 98%
See 1 more Smart Citation